The upstairs wife : an intimate history of Pakistan - Zakaria, Rafia, 1978- (Beacon Press, 2015)
"A memoir of Karachi through the eyes of its women. Rafia Zakaria's Muslim-Indian family immigrated to Pakistan from Bombay in 1962, feeling the situation for Muslims in India was precarious and that Pakistan represented enormous promise. And for some time it did. Her family prospered, and the city prospered. But in the 1980s, Pakistan's military dictators began an Islamization campaign designed to legitimate their rule--a campaign that particularly affected women. The political became personal for Zakaria's family when her Aunt Amina's husband did the unthinkable and took a second wife, a betrayal of kin and custom that shook the foundation of her family. The Upstairs Wife dissects the complex strands of Pakistani history, from the problematic legacies of colonialism to the beginnings of terrorist violence to increasing misogyny, interweaving them with the arc of Amina's life to reveal the personal costs behind ever-more restrictive religious edicts and cultural conventions. As Amina struggles to reconcile with a marriage and a life that had fallen below her expectations, we come to know the dreams and aspirations of the people of Karachi and the challenges of loving it not as an imagined city of Muslim fulfillment but as a real city of contradictions and challenges"--